2000
DOI: 10.1097/00004728-200003000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Visualization Modes for CT Colonography Using Cylindrical and Planar Map Projections

Abstract: The sensitivity of conventional CT colonography is limited by the percentage of the mucosal surface seen. Map projection CT colonography overcomes this problem and provides a more sensitive method with a high PPV for detecting polyps than other methods currently being investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 24 publications
2
49
0
Order By: Relevance
“…Several studies demonstrated, however, that alternative, comprehensive 3D review methods result in considerable shorter interpretation times than conventional fly-through virtual endoscopy review [12,13]. To our knowledge, at the present moment the literature on methods to review CT colonography [5][6][7][8][9][10][11][12][13] does not comprise reports on a comparison of a primary 3D review method with a primary 2D review method. Such a comparison is, however, entirely relevant as review methods are being debated for their potential role in the explanation of discrepant results in four large studies on CT colonography in low polyp prevalence patient groups [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated, however, that alternative, comprehensive 3D review methods result in considerable shorter interpretation times than conventional fly-through virtual endoscopy review [12,13]. To our knowledge, at the present moment the literature on methods to review CT colonography [5][6][7][8][9][10][11][12][13] does not comprise reports on a comparison of a primary 3D review method with a primary 2D review method. Such a comparison is, however, entirely relevant as review methods are being debated for their potential role in the explanation of discrepant results in four large studies on CT colonography in low polyp prevalence patient groups [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…As yet many investigators have developed methods to review CT colonography and tested these in small patient groups or phabtoms [5][6][7][8][9][10][11][12][13]. Despite the small body of evidence, the majority of CT colonography researchers use primary 2D reviews, probably based on practical grounds such as long review time and high computer requirements associated with 3D review.…”
Section: Introductionmentioning
confidence: 99%
“…Flattened versions of the colon surface may be a good complement for CT colonography or virtual colonoscopy; see [12,7] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…In almost all studies, CTC was based on the examination of CT images by an expert radiologist, using either the 2D images, 3D virtual colonoscopic views or both. Thus, until recently most efforts were directed towards developing better visualization and navigation techniques [4,[11][12][13][14][15][16][17][18][19]. Lately, more effort has been put into computer aided detection (CAD), whose ultimate goal is to identify polyps in a 3D CT data efficiently, and with high sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%